Effects of ZnO on piezoelectric properties of 0.01PMW-0.41PNN-0.35PT-0.23PZ ceramics. - Ha, JY; Choi, JW; Kang, CY; Choi, DJ; Kim, HJ; Yoon, SJ (ELSEVIER SCIENCE SA, 2005)
The microstructure and piezoelectric properties of the 0.01Pb(Mg1/2W1/2)O-3-0.41Pb(Ni1/3Nb1/3)O-3-0.35PbTiO(3)-0.23PbZrO(3)+0.1 and 0.3 wt.% Y2O3 + x ZnO ceramics were investigated. The crystal structure changed from psudocubic to tetragonal when ZnO added. The average grain size increased from 4 mum to 8 mum with the addition of ZnO by oxygen diffusion, even if the growth rate was low. When ZnO added until 0.5 wt.%, the epsilon(33)(T)/epsilon(0), kp and d(33) values of specimens were slightly increased regardless Y2O3 contents. The curie point of PMW-PNN-PT-PZ ceramics were increased from 162degreesC to 232degreesC, as increasing the ZnO contents. When ZnO added, the kp of specimens slightly was increased regardless Y2O3 contents. The mechanical quality factors were abruptly decreased regardless Y2O3 contents, when ZnO added until 0.75 wt.%. The optimized piezoelectric properties were obtained; d(33) = 730 (pC/N), k(p) = 60, Q(m) = 50, and epsilon(33)(T)/epsilon(0) = 4750, when PMW-PNN-PT-PZ + 0.3 wt.% Y2O3 + 0.5 wt.% ZnO sintered at 1200 degreesC for 1 h. (C) 2004 Elsevier B.V. All rights reserved.